Prince Mohammed Ali after the July Revolution 1952 and the Journey of Searching for the Lost - Yehia, Enas Fares.
This article discusses the status of Prince Mohammed Ali Tawfik, the owner of the famous Manyal Palace in Cairo after the outbreak of the July revolution; how the revolutionary council took all of his possessions leaving him poor; and how he tried by all means to find a solution for this great problem. The prince was a representative of the royal family in this matter. He paid many visits to London to reach a solution with the new regime in Egypt. This matter is important as it reveals the long journey of the royal family’s attempts to regain their property. This means that they did not accept their status as some thought, but they tried by all means to negotiate with Nasser and his council in this matter. The British government helped the prince a great deal after his departure from Egypt, but Nasser refused any intervention in this matter.